DESIGN AND SYNTHESIS OF NOVEL 4-(4-FLUORO-3-METHYLPHENYL)-6-(SUBSTITUTED ARYL)-1,6-DIHYDROPYRIMIDIN-2-OL DERIVATIVES AS POTENT ANTI-INFLAMMATORY AND ANALGESIC AGENTS - MURALIDHARAN V; RAJA S; ASHA DEEPTI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Pyrimidine heterocycles possessing hydroxy group has a unique place in medicinal chemistry and also plays a key role in biological processes. In the biological functions at cellular level pyrimidine plays imperative roles which lead the researchers to design a variety of its derivatives. The aim of the present study was to synthesize the novel set of 4-(4-fluoro-3-methylphenyl)-6-(substituted aryl)-1,6-dihydropyrimidin-2-ol derivatives. These compounds were screened for their analgesic and anti-inflammatory activities. Methods: A novel series of 4-(4-fluoro-3-methylphenyl)-6-(substituted aryl)-1,6-dihydro pyrimidin-2-ol derivatives were furnished in two steps starting from 4-fluoro-3-methyl acetophenone through chalcone formation. Human red blood cell membrane stabilization method and carrageenan-induced rat paw edema test were performed for screening in vitro and in vivo anti-inflammatory activity, respectively. Tail-flick technique was performed for screening analgesic activity. Results: All the synthesized 4-(4-fluoro-3-methylphenyl)-6-(substituted aryl)-1,6-dihydro pyrimidin-2-ol derivatives were characterized by Fourier-transform infrared spectroscopy,1H nuclear magnetic resonance, mass spectroscopy, and bases of elemental analysis. The result of biological screening revealed that many of the new derivatives were endowed with improved anti-inflammatory and analgesic activities. Conclusion: Nature of the substituent played a major role in anti-inflammatory and analgesic activities. The pyrimidine derivative with chlorophenyl substitution exhibited potent anti-inflammatory and analgesic activities. From the results, it was concluded that 6-(4-chlorophenyl)-4-(4-fluoro-3- methyl phenyl)-1,6-dihydropyrimidin-2-ol was the most active compound.